Aulas modernas: Nuevas perspectivas sobre las reformas de la enseñanza secundaria en la época de la JAE (1907-1939) - Aragón Albillos, Santiago (Historia de las Universidades, 2014)
The book "Modern classrooms. New perspectives on the reform of secondary education at the time of the JAE" aims to provide a renewed focus on the development of secondary education in Spanish society of the first third of the 20th century, focusing attention on reforms and innovations promoted by the Junta para Ampliación de Estudios e Investigaciones científicas (Board for Advanced Studies and Scientific Research) to improve the quality of that education level. The nine contributions in the work offer new knowledge about two important aspects of these reforms and innovations. On the one hand, new information about the renewing work of a large group of professors who introduced innovations in teaching practice of subjects such as natural history, geography, psychology, and language and literature. On the other hand, several case studies are presented to publicize the considerable effort made by the Spanish Second Republic to improve the quality of secondary education and increase decisively schooling rates by opening their classrooms to the women. In this multifaceted work have come together historians of science and education with the aim of helping better understand the Spanish public educational system and the history of their secondary education, which for too long has been the "poor cousin" of the historical-educational research. = El libro Aulas modernas. Nuevas perspectivas sobre las reformas de la enseñanza secundaria en la época de la JAE pretende ofrecer un renovado enfoque sobre el desarrollo de la enseñanza secundaria en la sociedad española del primer tercio del siglo XX, concentrando su atención en las reformas e innovaciones promovidas por la Junta para Ampliación de Estudios e Investigaciones Científicas para mejorar la calidad de ese nivel educativo. Las nueve contribuciones de la obra aportan nuevos conocimientos sobre dos aspectos significativos de esas reformas e innovaciones. Por una parte se ofrece relevante información sobre la labor de un amplio grupo de profesores que introdujeron innovaciones en la práctica docente de asignaturas como las ciencias naturales, la geografía, la psicología, y la lengua y literatura. Por otro lado se presentan diversos análisis de casos para dar a conocer el considerable esfuerzo efectuado por la Segunda República para elevar la calidad de la enseñanza secundaria e incrementar las tasas de escolarización abriendo sus aulas a las mujeres de manera decidida. Esta obra poliédrica, donde han confluido historiadores de la ciencia y de la educación, pretende por tanto ayudar a conocer mejor el sistema educativo público español y la historia de su educación secundaria que durante largo tiempo ha sido el "pariente pobre" de la investigación histórico-educativa.